2010
DOI: 10.1016/j.jasms.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight secondary ion mass spectrometry imaging demonstrates the specific localization of deca-bromo-diphenyl-ether residues in the ovaries and adrenal glands of exposed rats

Abstract: Deca-bromo-diphenyl ether (DBDE) is one of the most efficient brominated flame retardant (BFR) available on the market. We recently demonstrated that when administered to female rat by oral route, DBDE is efficiently absorbed, with the highest residual concentrations found in two endocrine glands, namely the adrenal glands and the ovaries. Time-of-flight secondary ion mass spectrometry (TOF-SIMS) imaging, a technique usually used for the study of endogenous compounds, was applied for the first time to a persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…Some PBDEs, for example decabromo-diphenyl ether, have found to be accumulated in adrenal glands and the ovaries, possibly causing endocrine-disrupting effects in mammals. 27 The current study demonstrated that BDE3 caused an increase in serum CORT and ALDO levels during puberty. Excessive ALDO levels can cause a disease such as Conn's syndrome, which exhibits high blood pressure and heart damage.…”
Section: ■ Discussionsupporting
confidence: 52%
“…Some PBDEs, for example decabromo-diphenyl ether, have found to be accumulated in adrenal glands and the ovaries, possibly causing endocrine-disrupting effects in mammals. 27 The current study demonstrated that BDE3 caused an increase in serum CORT and ALDO levels during puberty. Excessive ALDO levels can cause a disease such as Conn's syndrome, which exhibits high blood pressure and heart damage.…”
Section: ■ Discussionsupporting
confidence: 52%
“…Furthermore, Seyer et al (2010) demonstrated more specifically, this distribution is limited to the adrenal cortex. The extreme lipophilicity and planar structure of DBDPE may also result in its preferential distribution to the adrenal gland.…”
Section: Discussionmentioning
confidence: 92%
“…Cortical hyperplasia of the adrenal glands may be correlated with an increased production of cortisol, which in turn triggers the down regulation of the immune system. Given the structural similarity between PCBs, decaBDE, and DBDPE, it is noteworthy that decaBDE residues mainly target the outer part of the adrenal cortex (Seyer et al, 2010). Why these residues specifically accumulate in this part of the adrenal glands while, in contrast, the medulla is not a target for decaBDE, remains to be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…Localization to the adrenal gland is less intuitive, although the impact of endocrine disrupting chemicals (like BEH-TEBP and other BFRs) on steroid synthesis may eventually yield an explanation of the phenomenon. Imaging studies have shown decaBDE localizes to the adrenal cortex and ovarian stroma in exposed rats although it was unclear whether brominated components detected in the cortex were present as parent chemical or metabolites (Seyer et al, 2010). Other studies of [ 14 C]-labeled xenobiotics found adrenal extracts co-eluted with cholesteryl ester with evidence for their degradation and incorporation into endogenous substances (Darnerud and Brandt, 1985).…”
Section: Discussionmentioning
confidence: 99%